Myanmar Rice and Pulses : Farm Production Economics and Value Chain Dynamics - World Bank (World Bank, Washington, DC, 2020)
Agriculture continues to play a very important role in Myanmar’s economy. For many years, understanding the dynamics and performance of Myanmar’s agriculture has been difficult due to the absence of reliable, up-to-date data, at sectoral, sub-sectoral, or microeconomic level. During the past five years, significant changes have occurred in Myanmar’s demographics, economy, and public spending and in its integration into world and regional markets for agro-food products. While Myanmar’s agriculture has experienced some considerable diversification over the past decade, rice, and bean or pulses remain core elements of the sector. Rice remains an important crop and commodity for the economy and welfare of Myanmar. Myanmar’s paddy production has realized modest gains, yet it continues to under-perform, relative to peers and to its potential. One positive development at the production level has been a significant increase in labor productivity. One potentially disturbing trend has been a significant increase in agro-chemicals use in paddy production. Elsewhere in the rice value chain, many functions are characterized by low levels of operational efficiency and/or inadequate quality management. Myanmar is the world’s third largest producer of pulses, after India and Canada. Myanmar is also a major exporter of pulses globally and the largest in the ASEAN region. After several years of promising trade results, the pulses sub-sector experienced major problems in 2017 following India’s imposition of import restrictions on back gram, chick peas and other commodities. While the trade restrictions have exposed the vulnerability of the pulses sector due to its heavy reliance on a single market for some products, there are additional challenges faced by the sector. Elsewhere in the pulses value chain, there has been limited investment or value addition.